Deliberative Convergence: Citizen Participation in Constitutional Change, Chile 2016 [Convergencia Deliberativa: La Participación Ciudadana en el Cambio Constitucional, Chile 2016 - Figueroa-Rubio, P (Societa Editrice Il Mulino, 2021)
This study examines the case of the Constituent Process Open to Citizens in Chile (2016), as a methodology for constitutional change. Research on the incidence of constitutional processes in the result of the constitutional text indicates that the process of constitutional change is key in the expected results, and that participatory methodologies must have certain characteristics to obtain results (Ginsburg, et.al. 2009; Bonar, 2017; Soto & Welp, 2019). From the theory of deliberative democracy and the participatory elaboration of the Constitution, this work analyzes the design and implementation of the participatory stage for the constitutional change carried out in Chile in 2016. Through the examination of the Deliberative Convergence methodology and the scope of its implementation, the implementation of this institutional design of public deliberation as a mechanism for constitutional change is studied. This work proposes that the Deliberative Convergence methodology had as its objective the public incidence of citizen participation, conceived from a deliberative perspective, considering incident public participation in all its stages. © 2021 Societa Editrice il Mulino. All rights reserved.